California Women Lawyers Annual Dinner in San Diego - Watkins, Howard::::::::: (1989)
Hon. Judith Chirlin, Maggie Crosby and her Fay Stender Award, Doris Coleman and California Women Lawyers President Janice Kamenir-Reznik